Associations between sleep disturbances, mental health outcomes and burnout in firefighters, and the mediating role of sleep during overnight work: A cross‐sectional study. (26th May 2019) - Wolkow, Alexander P.; Barger, Laura K.; O'Brien, Conor S.; Sullivan, Jason P.; Qadri, Salim; Lockley, Steven W.; Czeisler, Charles A.; Rajaratnam, Shantha M. W.
Abstract: This study investigated whether sleep disorder risk and mental health outcomes in firefighters were associated with burnout, particularly emotional exhaustion, and examined the mediating role of sleep at work in these relationships. A secondary aim was to investigate associations between habitual sleep characteristics and burnout. North American firefighters ( n  = 6, 307) completed the Maslach Burnout Inventory (emotional exhaustion, depersonalisation, personal accomplishment), and were screened for sleep disorders and self‐reported current mental health conditions and sleep characteristics. Multiple logistic regression analyses examined associations between sleep, mental health outcomes and burnout. Firefighters screening positive for a sleep disorder, particularly insomnia, had increased risk of emotional exhaustion (adjusted odds ratio 3.78, 95% confidence interval 2.97–4.79). Firefighters self‐reporting a current mental health condition were at greater risk of emotional exhaustion (adjusted odds ratio 3.45, 95% confidence interval 2.79–4.27). Sleep during overnight work mediated the impact of having a sleep disorder and mental health condition on high burnout. Sleepiness and sleep deficit (difference between required and actual sleep), even in firefighters without sleep disorder risk, were associated with depersonalisation (adjusted odds ratio 1.65, 95% confidence interval 1.34–2.03 and adjusted odds ratio 1.29, 95% confidence interval 1.06–1.57, respectively) and low personal accomplishment (adjusted odds ratio 1.25, 95% confidence interval 1.07–1.47 and adjusted odds ratio 1.17, 95% confidence interval 1.01–1.35, respectively). Sleep and mental health problems were associated with increased risk of burnout in firefighters, and sleep during overnight work mediated these relationships. The results suggest the need to examine the effectiveness of occupational interventions that improve the opportunity for sleep, together with screening for and treating sleep disorders, to reduce burnout risk.